# Integral of Logarithmic Function to Any Base : Log_a (x)

\( \) \( \)\( \)\( \)\( \)\( \)
The steps to find the integral of a logarithmic function to any base are presented.

## Use of the Change of Base Formula

Let \( y = \log_a x \)

Use the change of base formula to rewrite \( y = \log_a x \) using the natural logarithm \( \ln \) as

\( y = \log_a x = \dfrac{\ln x}{\ln a} \)

We now evaluate the integral

\( \displaystyle \int \log_a x \; dx = \int \left(\dfrac{ \ln x }{\ln a}\right)\; dx \)

\( \ln a \) is a constant and therefore

\( \displaystyle \int \log_a x \; dx = \dfrac{ 1}{\ln a} \int \ln x \; dx \qquad (I) \)

The integral of ln x is given by

\( \displaystyle \int \ln x \; dx = x \ln x - x + c \)

Substitute in \( (I) \) to obtain

\[ \displaystyle \int \log_a x \; dx = \dfrac{ 1}{\ln a} (x \ln x - x) + c \]

## More References and Links

- change of base formula
- Integral of ln x
- Chain Rule of Differentiation in Calculus
- Convert Logarithms and Exponentials
- Rules of Logarithm and Exponential - Questions with Solutions